Formation of the theoretical model of development of basketball in Ukraine with consideration of the infl uence of factors of globalization of high performance sport - Руслана Сушко (National University of Physical Education and Sport of Ukraine, 2017)
The features of the development of basketball in the context of globalization of high performance sport are reviewed and analyzed based on the influence of the following factors: socialization of athletes and politicization of official international competitions, professionalization and commercialization of national and international official competitions, migration of basketball players and their concentration in national and international leagues and the world's best sports training centers. The migration of the athletes of different levels as the main influencing factor of globalization of high performance sport is characterized.The background for building a model of basketball development is outlined; methodological and theoretical knowledge level for building a model of basketball development in Ukraine in conditions of the impact of global trends on high performance sport is identified.